Efficacy and safety of Daoyin and massage for lumbar disc herniation: A protocol for overview of systematic reviews. Issue 5 (4th February 2022) - Shi, Mingpeng; Zhang, Xianshuai; Wang, Siyi; Li, Shaojun; Zhao, Changwei; Li, Zhenhua; Li, Jianan
Abstract: Background: Lumbar disc herniation (LDH) is a common disease, which can cause low back pain, sciatica, and even disability. The treatment of LDH is a global challenge. Conservative therapy with non-drugs is considered to be the first choice for patients with LDH. In recent years, an increasing number of systematic reviews and meta analyses on Daoyin and massage interventions in lumbar disc herniation have been implemented. However, the evidence quality and methodological quality of these systematic reviews/meta analyses are unknown and need to be systematically evaluated. This overview aims to systematically summarize and critically appraise the current evidence on Daoyin and massage for LDH. Methods: Eight electronic data will be retrieved, including China National Knowledge Infrastructure (CNKI), Wanfang database (WF), China Biomedical database (CBM), Chinese Scientific Journals Database (VIP), PubMed, Cochrane Library, Web of Science (WOS), and EMBASE from their inception to March 1, 2022. The reporting quality, methodological quality, risk of bias, quality of evidence will be assessed by using The Preferred Reporting Items for Systematic Reviews and Meta-analyses 2020 (PRISMA 2020), the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic Review (ROBIS), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Two independent researchers conducted literature screening, data extraction, and quality evaluation process. In addition, we will establish an overlap matrix and calculate the corrected covered area to evaluate the impact of overlapping areas on conclusions. Results: The results will be published in a peer-reviewed journal. Conclusion: This overview will provide comprehensive evidence of Daoyin and massage for treating lumbar disc herniation. Systematic review registration: INPLASY202210019.